2013
DOI: 10.1155/2013/853095
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Potential Malignant Transformation in Recurrent Calcifying Cystic Odontogenic Tumor: Review of the Literature

Abstract: Calcifying cystic odontogenic tumor (CCOT) demonstrates considerable diversity in histopathology and clinical behavior. Ghost cell odontogenic carcinoma (GCOC) is the rare malignant counterpart of CCOT and it frequently arises from malignant transformation of a recurrent CCOT. In this paper, we present a case of CCOT and discuss its distinct histopathologic features in recurrence. Then, we will have a review on clinical, histopathological, and immunohistochemical aspects of GCOC in the literature. Predictive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(33 reference statements)
0
8
0
Order By: Relevance
“… 9 GCOC can present de novo , however, it may also present as a malignant transformation of recurrent CCOT or DGCT. 3 , 4 The ability of CCOT or DGCT to transform into the malignant variant, GCOC, has been linked to level of expression of Ki-67, a biomarker of cell proliferation. In almost all reported studies, Ki-67 is weakly expressed in CCOT or DGCT, however, expression is strong in GCOC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 GCOC can present de novo , however, it may also present as a malignant transformation of recurrent CCOT or DGCT. 3 , 4 The ability of CCOT or DGCT to transform into the malignant variant, GCOC, has been linked to level of expression of Ki-67, a biomarker of cell proliferation. In almost all reported studies, Ki-67 is weakly expressed in CCOT or DGCT, however, expression is strong in GCOC.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 In general, these neoplasms have a very unpredictable course that ranges from indolence to potential fatality. 1 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Painful swelling with local paraesthesia is the most common symptom of ghost cell odontogenic carcinoma [ 12 ]. Some authors reported of infiltrative growth, root resorption and tooth displacements in cases of GCOC [ 16 , 17 ]. Radiographic examinations showed a mixed radiolucent-radiopaque lesion with a moderately defined border.…”
Section: Resultsmentioning
confidence: 99%
“…A calcifying odontogenic cyst (COC) is a benign developmental cystic lesion with rare malignant transformation documented in the literature. COC is a hybrid lesion of the jaw exhibiting a diverse variety of clinical behaviours and histopathological features including cystic, solid (neoplastic) and aggressive variations.…”
Section: Introductionmentioning
confidence: 99%